Park quality and chronic disease: A city-level analysis - Lauren S. Pongetti, OTR/L; Fazlay S. Faruque, PhD; Benjamin H. Walker, PhD (Wellbeing, Space and Society)
Introduction: Chronic diseases are the leading cause of death and disability in the United States, with disproportionate burdens in urban areas. Urban parks and green spaces may play a protective role in chronic disease prevention, yet few studies have examined how city-wide park quality relates to chronic disease outcomes. This study investigates the relationship between ParkScore, a composite measure of park quality, and the prevalence of eight chronic diseases across 93 of the most populated U.S. cities from 2017 to 2019. Methods: Using mixed-effects regression models with repeated measures nested within cities, we examined associations between ParkScore and age-adjusted prevalence of high blood pressure, cancer, coronary heart disease, chronic obstructive pulmonary disease, diabetes, chronic kidney disease, obesity, and stroke. Results: Results revealed significant inverse relationships between ParkScore and four chronic diseases: high blood pressure, cancer, coronary heart disease, and chronic obstructive pulmonary disease. No significant associations were found for diabetes, obesity, chronic kidney disease, or stroke. Additionally, sociodemographic variables including access to health insurance, income, education, race and ethnicity were significantly associated with disease prevalence. Conclusion: These findings support growing evidence that park quality may be an important component of chronic disease prevention in urban environments. Additionally, findings support the development and maintenance of quality parks as urban planning strategies aimed at improving public health. Further research is warranted to explore causal pathways, disparities in park access, and the role of parks in addressing complex, multi-factorial chronic diseases.